Statistical aspects of occupational injuries in the production of chemical products and chemicals - Konovalova, Viktoria; Evtushenko, Olga; Siryk, Alina (My University, 2021)
The study was conducted on the basis of the nominal-statistical method in the study of many random divisions in systematic works, according to statistical data on occupational injuries in the production of chemicals and chemical products for the period from 2010 to 2019. The study of trends in time series of occupational injuries is based on data from the State Statistics Service of Ukraine. Дослідження проводилось на основі номінально-статистичного методу при вивченні багатьох випадкових поділів у систематичних роботах, згідно статистичних даних про виробничий травматизм у виробництві хімічних речовин та хімічних продуктів за період з 2010 по 2019 рік. Тенденції часових рядів виробничого травматизму ґрунтуються на даних Державної служби статистики України.
Keywords: кафедра екології та екоменеджменту; statistics; occupational injuries; production of chemical products; статистика; професійний травматизм; виробництво хімічних продуктів